How to Face Chronic Liver Disease: The Sinusoidal Perspective - Fernández-Iglesias, Anabel; Gracia-Sancho, Jordi (Frontiers in Medicine, 2017)
Liver microcirculation plays an essential role in the progression and aggravation of chronic liver disease (CLD). Hepatic sinusoid environment, mainly composed by hepatocytes, liver sinusoidal endothelial cells, kupffer cells and hepatic stellate cells, intimately cooperate to maintain global liver function and specific phenotype of each cell type. However, continuous liver injury significantly de-regulates liver cells protective phenotype, leading to parenchymal and non-parenchymal dysfunction. Recent data have enlightened the molecular processes that mediate hepatic microcirculatory injury, and consequently, opened the possibility to develop new therapeutic strategies to ameliorate liver circulation and viability. The present review summarizes the main cellular components of the hepatic sinusoid, to afterwards focus on non-parenchymal cells phenotype de-regulation due to chronic injury, in the specific clinical context of liver cirrhosis & derived portal hypertension. Finally, we herein detail new therapies developed at the benchside with high potential to be translated to the bedside.